Pump station information processing platform based on internet - LYU YAJUN; CHEN JUN (2018)
In this application a pump station information processing platform based on internet, including control platform (1) and pump station (2), pump station (2) upper portion is equipped with control platform (1), be equipped with on the panel on control platform (1) upper portion touch -sensitive screen (3), the top edge transverse arrangement of touch -sensitive screen (3) has pilot lamp (4), the topedge transverse arrangement of touch -sensitive screen (3) has control switch (5), be connected with on logic controller (14) in control platform (1) signal converter (6), signal converter (6) outwards are connected with monitor platform (7) through the net twine, have the receipt of integrated nature, the unity is monitored, has overcome the integrated problem of miniature water treatment, unifies the control to a plurality of little treatment facilities. 本申请中所述的种基于互联网的泵站信息处理平台，包括控制平台(1)以及泵站(2)，泵站(2)上部设有控制平台(1)，控制平台(1)上部的面板上设有触摸屏(3)，触摸屏(3)的上边缘横向排列有指示灯(4)，触摸屏(3)的上边缘横向排列有控制开关(5)，控制平台(1)中的逻辑控制器(14)上连接有信号转换器(6)，信号转换器(6)